HABITAT DAN PERILAKU SOSIAL BURUNG KAKATUA TANIMBAR (Cacatua goffiniana) DI DESA LORULUN KECAMATAN WERTAMRIAN KABUPATEN KEPULAUAN TANIMBAR - Sinaga, Grace Tasya; Pattinasarany , Cornelis; Tuhumury , Andri (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This research aims to determine the habitat conditions and behavior of the Cacatua goffiniana in Lorulun Village, Tanimbar Islands Regency.  The method used for vegetation community data is a combination of the path method and plotted lines at 4 growth levels including seedlings, saplings, poles and trees, there are 15 paths with 75 plots in 3 observation blocks.  Determining the location for observing the behavior of the Tanimbar Cockatoo (Cacatua goffiniana) was carried out using the concentrated point method and also the All Occurrences method.  The research results show that the main habitat of the Tanimbar Cockatoo (Cacatua goffiniana) is primary and secondary tropical forests which have the availability of tall trees for nests and food sources.  This bird is also found in plantations and forest edge areas, showing adaptability to habitat changes.  The social behavior of Tanimbar cockatoos is very complex, showing a high level of intelligence, often seen in activities in small groups of 5-10 individuals.  Social interactions between these individuals include various behaviors such as coordinating vocalization behavior, vocalization behavior feeling threatened, aggressive agonistic behavior, submissive agonistic behavior, affiliative behavior of feather probing, affiliative behavior of mutual probing, affiliative behavior of playing, affiliative behavior of perching.  This research also notes the existence of a strong territorial behavior pattern, groups of Tanimbar parrots will defend their territory from other groups when food sources are abundant, these territorial boundaries become more flexible.